Effects of production stage and fertility traits on milk production of pasture-grazed Holstein and Jersey cows in a Mediterranean-type climate region - Bangani, N.M.; Muller, C.J.C.; Dzama, K.; Cruywagen, C.W.C; Imbayarwo-Chikosi, V.E. (South African journal of animal science, 2022)
The aim of this study was to compare the milk production of Holstein and Jersey cows on pasture as affected by parity, lactation stage, calving season, age at first calving, and calving interval. Test-day lactation records of 122 Holstein and 99 Jersey cows, varying from parities 1 to 6, were collected using standard milk recording procedures. Cows were managed and kept as one herd on kikuyu over-sown with ryegrass pasture and received 7 kg of concentrate (as fed) containing 170 g/kg crude protein per day. Across parities, the means for milk yield, milk fat, milk protein, dry matter intake, and body weight were 23.8 ± 6.2 and 17.9 ± 4.4 kg/day; 3.89 ± 0.03 and 4.66 ± 0.03%; 3.17 ± 0.02 and 3.59 ± 0.02%; 17.8 ± 2.6 and 14.4 ± 2.1 kg/day; and 567 ± 3.49 and 411 ± 3.84 kg for Holstein and Jersey cows, respectively. Milk yield increased by 26.5% in Holsteins and 23.7% in Jerseys from first to fourth lactation. Mean lactation number was 2.5 ± 0.15 and 3.0 ± 0.17; test-day milk yield for summer was 21.2 ± 0.28 and 16.5 ± 0.31 kg/day; and winter was 21.3 ± 0.28 and 16.4 ± 0.32 kg/day; age at first calving was 26.4 ± 0.3 and 26.2 ± 0.3; and inter-calving period was 13.9 ± 0.18 and 13.2 ± 0.17 months, for Holstein and Jersey cows, respectively. With inter-calving periods of 13 months, 13.1 to 15.0 and above 15 months, the 305-day Holstein cow milk yield was 7324 ± 181, 7768 ± 193, and 7927 ± 211 kg, whereas that of Jerseys was 5400 ± 135, 5621 ± 244, and 5724 ± 234 kg, respectively. In this study, Jerseys performed better than Holsteins in lactation number and calving interval. Holsteins, however, had a higher increase in milk yield from first to fourth lactation, whereas age at first calving did not differ.